Hypoalbuminemia and Risk of Portal Vein Thrombosis in Cirrhosis - Roberto Cangemi; Valeria Raparelli; Giovanni Talerico; Stefania Basili; Francesco Violi; Palasciano Giuseppe; D’Alitto Felicia; Palmieri Vincenzo Ostilio; Santovito Daniela; Di Michele Dario; Croce Giuseppe; Sacerdoti David; et al. (Gastro Hep Advances, 2024)
Background and Aims: Hypoalbuminemia, as defined by serum albumin (SA) levels ≤35 g/L, is associated to venous and arterial thrombosis in general population and in patients at risk of cardiovascular disease. It is unknown if SA ≤35 g/L is also associated to portal vein thrombosis (PVT) in cirrhosis. Methods: Cirrhotic patients enrolled in the Portal vein thrombosis Relevance On Liver cirrhosis: Italian Venous thrombotic Events Registry (PRO-LIVER) study (n = 753), were followed-up for 2 years to assess the risk of PVT, that was diagnosed by Doppler ultrasonography. Child-Pugh classes, Model for End-Stage Liver Disease score, presence of hepatocellular carcinoma and laboratory variables including SA, D-dimer, and high-sensitivity C-reactive protein (hs-CRP) were measured at baseline. Results: SA ≤35 g/L was detected in 52% of patients. A logistic multivariate regression analysis showed that higher Child-Pugh class, hepatocellular carcinoma and thrombocytopenia were significantly associated to SA ≤35 g/L. In a subgroup of patients where data regarding hs-CRP and D-dimer were available, SA ≤35 g/L was inversely associated with hs-CRP and D-dimer. During the follow-up, a total of 61 patients experienced PVT. A Kaplan Meier survival analysis showed SA ≤35 g/L was associated to increased risk of PVT compared to SA >35 g/L (P = .005). A multivariate Cox proportional hazards regression analysis showed that male sex, lower platelet count, and SA ≤35 g/L remained associated to PVT after adjusting for confounding factors. Conclusion: Cirrhotic patients with SA ≤35 g/L are at higher risk of experiencing PVT compared to those with SA >35 g/L and could be considered as potential candidates to anticoagulant prophylaxis for PVT prevention.